The Acheulean of the Upper Guadiana River Basin (Central Spain). Morphostratigraphic Context and Chronology - Santonja, M.; Pérez-González, A.; Baena, J.; Panera, J.; Méndez-Quintas, E.; Uribelarrea, D.; Demuro, M.; Arnold, L.; Abrunhosa, A.; Rubio-Jara, S. (Frontiers in Earth Science, 2022)
In the upper basin of the Guadiana River, especially in the sectors drained by its right-bank tributaries, the Bullaque and Becea rivers, important concentrations of Acheulean and Mousterian industries can be found in a superficial position. These industries have provided series containing tens of thousands of pieces. Deposits in stratigraphic position have also been identified, related to the fluvial terraces of the Guadiana and Jabalón rivers and some tributaries. Within the sector studied, in the province of Ciudad Real, the position of these deposits is related to alluvial fans developed on the slopes of the immediate reliefs. These fans, mainly composed of Lower and Middle Ordovician quartzite gravel, were eroded in their distal positions by the Bullaque and Becea rivers, forming very low terraces on which large concentrations of Acheulean and Mousterian lithic industry can be found. El Sotillo, the only known stratigraphic site in the area, was excavated in 2017-2019 and consists of several levels with Mousterian and Acheulean industry. We present the technological characteristics of the main Acheulean assemblage recognised at this site, for which numerical dates have been obtained placing its chronology in the second half of the Middle Pleistocene. The location of these sites, in surficial position and El Sotillo, allows us to recognise a territorial space with specific geographic characteristics and a very significant human impact.